Urgensi Munasabah Dalam Menyingkap Hikmah Susunan Ayat Al-Qur’an - Hakmi Hidayat; Nihayatul Ulya; Nadia Salma; Saskia Anggun Fatimah As-Zuhra (GLOBAL SCIENTS PUBLISHER, 2025)
The Qur'an is a holy book that was revealed with a very distinctive structure, not only in terms of language, but also in the arrangement of its verses and chapters. One important approach in understanding this structure is the science of munāsabah, which is the science that studies the relationship and interconnectedness between verses or chapters in the Qur'an. This article aims to examine the urgency of munāsabah in revealing the wisdom behind the arrangement of the verses of the Qur'an and its contribution to enriching the understanding of interpretation. The results of the study show that munāsabah not only plays a role in beautifying the narrative of the Qur'an, but also uncovers deeper meanings, including moral, legal, and spiritual messages hidden in the sequence of revelation. Awareness of the importance of munāsabah can encourage a more contextual and integrative approach to interpretation in contemporary Qur'anic studies.